Josephine Lang : her life and songs - Krebs, Harald, 1955- (Oxford University Press, 2007)
Josephine Lang (1815-80) was one of the most gifted, respected, prolific, and widely published song composers of the nineteenth century, yet her life and works have remained virtually unknown. Now, this carefully researched, compelling, and poignant study recognizes the composer for her remarkable accomplishments. Based on years of study of unpublished letters, musical autographs, reviews, and the autobiographical poetry of Lang's husband, Reinhold Kostlin, the biographical portions of the book offer a stunning portrait of the composer as a woman and an artist. In-depth musical analyses interwoven with the biography will be illuminating to scholars and to musicians of all skill levels. The analyses reveal Lang's sensitivity to her chosen poetic texts, as well as the validity of her claim that her songs were her diary; the authors demonstrate that many of the songs are directly connected to the events of Lang's life. The analyses are illustrated by an abundance of musical examples, including a number of complete songs. A companion CD, on which the authors have recorded 30 songs by Lang, complements the text.